Advances in Auricular Point Pressing plus Music Therapy for Subjective Tinnitus - Ye, Ziyun; Zhang, Xiong (Journal of Contemporary Medical Practice, 2026)
Subjective tinnitus is a common and intractable otological disease in clinical practice. Patients perceive abnormal sounds in their ears without external sound sources. This condition features a long course and high recurrence rate, and is often accompanied by anxiety, insomnia and other problems, which greatly impair patients’ quality of life. Conventional Western medical monotherapies such as medication and sound masking yield poor long-term outcomes, and there is no radical cure available so far. Auricular point pressing therapy in traditional Chinese medicine (TCM), based on the auricular holographic theory, can dredge meridians, regulate qi and blood, and balance yin and yang. Music therapy can reshape auditory pathways and regulate emotions through auditory intervention. The combination of the two therapies can regulate physical conditions, repair the central nervous system and relieve negative emotions, serving as a distinctive integrated TCM and Western medicine regimen for tinnitus treatment. This paper reviews relevant domestic and overseas studies in recent years, summarizing the pathogenesis of tinnitus from both TCM and Western medicine perspectives, the individual efficacy and synergistic mechanism of the two therapies, as well as their current clinical application. It also analyzes existing problems in current researches and puts forward prospects, aiming to provide references for the standardized, targeted application and further in-depth study of this combined therapy.